Implementasi Program Rugby Masuk Sekolah (RMS) Berbasis T1 Rugby di Yogyakarta - Abdul Mahfudin Alim; Agus Supriyanto; Sunaryo; Agung Wahyu x Nugroho (Laksana Olahraga, 2026)
The Rugby Masuk Sekolah (RMS) program is an educational initiative aimed at introducing a safe and low-contact version of rugbyT1 Rugby to students and physical education teachers in the Special Region of Yogyakarta, Indonesia. The program’s primary goal is to enhance knowledge, skills, and instill character building values such as integrity, discipline, and respect. Implemented over a three-month period, the program adopted a participatory approach involving theoretical and practical training, teaching demonstrations, school based implementation support, evaluation, and a Student Rugby Festival. A mixed-methods evaluation was used, combining quantitative analysis of teacher practice and student knowledge tests with qualitative interviews. Results indicated a significant improvement in students’ knowledge and skills were good (average score of 85.78) and teachers’ practical performance was good (average score of 80.24). The program received positive reception from schools and communities and succeeded in shifting negative perceptions of rugby. Despite challenges such as limited facilities and concerns over physical contact, the RMS program demonstrated the effectiveness of T1 Rugby as an educational and character-building tool in school physical education in Indonesia.